Formulasi dan Evaluasi Fisik Sediaan Granul Stevia Sebagai Pemanis Alami Dengan Penambahan Polivinilpirolidon (PVP) Sebagai Pengikat - Al-Hakim, Nur Achsan; Ratih , Hestiary; Sabrilla , Niken (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
The development of natural sweetener discoveries continues to be carried out to realize healthy living behavior in its use in food and beverage products, including in the formulation of pharmaceutical preparations. Stevia (Stevia rebaudiana) is a plant that contains high sweetness and has the lowest caloric value. This study aims to formulate and physically evaluate stevia extract granule preparations using the wet granulation method with the addition of varying concentrations of Polyvinylpyrrolidone (PVP) as a binder, F0 (without PVP), F1 (1%), F2 (3%), and F3 (5%). Physical evaluation of stevia granule preparation includes organoleptic test, moisture content, flow rate, angle of repose, compressibility index and granule dissolving time in water. The results of the physical evaluation of granule preparations during 28 days storage showed that F3 was the best formula compared to other formulas, as evidenced by the results of statistical analysis using the one-way ANOVA method showing significant differences (p<0.05) between formulations. The evaluation results obtained were moisture content (<3%), flow rate (10.23 g/sec), angle of repose (27°), compressibility index (10%) and granule dissolving time (<1 minute). This study shows that the use of 5% PVP concentration in F3 as a binder can improve the physical properties of stevia granule preparations to be better than 1% and 3% concentrations.